Pengaruh Kualitas Aset Terhadap Profitabilitas Pada Perbankan Syariah Di Indonesia - Silvia, Sineba Arli (Institut Agama Islam Negeri (IAIN) Curup, 2017)
The healthy bank is very important because they manage public’s funds that entrusted to them by measuring the asset quality of the bank. Asset quality is a very important component, due to poor asset quality has proven to be the cause of failure of the bank, despite the obvious cause not only liquidity or stock. This research aimed to analyze the effect of asset quality toward the profitability of Islamic Banking in Indonesia. This research examines the effect of the variable of quality of productive assets (KAP) and Non-Performing Financing (NPF) toward the Return on Assets (ROA). The population of this research is the general Islamic Banks (BUS ) from 2010 to 2015. This research uses purposive sampling to determining the sample. The sample used in this research is the general Islamic banks that publish annual reports on the period 2010-2015. With certain criteria, there is 8 BUS sample. The data research is secondary data obtained from the website of each bank. While the method of data analysis uses multiple linear regression analysis. The results of this research showed that the variables of KAP and NPF had the effect toward ROA amounted 18.1 percent, with the significance level of 0.050. KAP variable partially had positive and significant impact toward ROA of Islamic Banking in Indonesia (0.034